2019
DOI: 10.4018/ijaci.2019070102
|View full text |Cite
|
Sign up to set email alerts
|

Web Text Categorization Based on Statistical Merging Algorithm in Big Data Environment

Abstract: In the field of modern information technology, how to find information quickly, accurately and comprehensively that users really needed has become the focus of research in this field. In this article, a feature selection method based on a complex network is proposed for the structure and content characteristics of large-scale web text information. The preprocessed web text is converted into a complex network. The nodes in the network correspond to the entries in the text. The edges of the network correspond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The proposed method achieved an accuracy of 92.40% but is computationally expensive. Accordingly, due to the effectiveness of the proposed approach, it is suggested to compare the proposed approach with other feature selection methods for benchmarking and other previous studies on dermoscopic images, such as in [28][29][30][31][32]. In the future, we intend to migrate this method to a mobile application.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed method achieved an accuracy of 92.40% but is computationally expensive. Accordingly, due to the effectiveness of the proposed approach, it is suggested to compare the proposed approach with other feature selection methods for benchmarking and other previous studies on dermoscopic images, such as in [28][29][30][31][32]. In the future, we intend to migrate this method to a mobile application.…”
Section: Resultsmentioning
confidence: 99%
“…The supervised approach ( Turney, 2002 ) transforms the keyphrase extraction work into a classification or regression problem ( Wang & Wang, 2019 ). It employs the learned model to identify if a candidate phrase in a text is a keyphrase by training it on the labeled training set.…”
Section: Methodsmentioning
confidence: 99%
“…Authors in [30] found numerous aspects in the data collected by victims, such as negative feelings, isolation, and repeated pattern of fear terms. The authors in [31] used behavioral trends on Facebook to predict depression following violence incidence by self-reported victims through their Facebook status. They performed t-tests to distinguish the victims' behaviors in first violence incidence and in the repeated ones.…”
Section: Predicting Violence-induced Stress Incidents Through Questio...mentioning
confidence: 99%
“…These data were used in the learning random forest classifiers to identify violence victims from non-victims. Authors in [29][30][31][32] collected data from Twitter to predict violence incidence from tweeter. Authors in [33], employed analysis dynamics in physician rating websites during the early wave of the COVID-19 pandemic.…”
Section: Predicting Violence-induced Stress Incidents Through Questio...mentioning
confidence: 99%